Strategi Pencegahan Stunting dalam Rumah Tangga untuk Mendukung Pembangunan Berkelanjutan di Kota Tasikmalaya - Agustian, Dita; Triyanto, Samuel Agus; Apriyani, Dwi; Helbawanti, Octaviana (FKIP Universitas Sebelas Maret, 2023)
Stunting reduction and sanitation have been essential goals in national sustainable development. Nutrition and sanitation education is critical to prevent stunting because children’s growth requires optimal nutrition and a healthy environment. A community service activity was conducted under the health scheme supported by Universitas Siliwangi for 2022 (PbM-SK) in collaboration with the women association members in Sambongsari Village, Tasikmalaya, West Java. Eighteen organisation members who participated in the activity. They were given counselling about the causes of stunting, the impact of stunting, the fulfilment of nutrition, and the effects of sanitation. The purposes of community service activities were to understand the causal factors, the characteristics of stunting, the impact of stunting, and healthy sanitation. Public awareness to consume food containing protein, calcium, and vitamin D, which are essential nutrients. Problems in households with toddlers with chronic diseases such as tuberculosis (TB) are usually less able to distinguish the causes and treatment of diseases with stunting conditions because there are physical growth disorders. Thus, education to prevent stunting is essential so that public understanding is more optimal on the prevention and proper handling of toddlers with stunting characteristics and toddlers who experience certain diseases. The evaluation of stunting and sanitation knowledge in Sambongpari, Tasikmalaya City, showed increased public understanding of stunting and sanitation. However, it was not significant, namely the average value of 36.5 to 68.6. Stunting management strategies closely related to children’s golden period, namely specific nutrition interventions for the First 1,000 Days of Life, can determine brain growth, intelligence, height, and vulnerability to chronic disease risk.